LITERASI DAN EFIKASI KEUANGAN TERHADAP MINAT MAHASISWA BERINVESTASI DI PASAR MODAL - Tri Pangestika; Ellen Rusliati (Faculty of Economic and Business, University of Pasundan, 2019)
This study aims to determine how the literacy and financial efficacy of interest in investing in the capital market. Data collection and library techniques are already done by giving questionnaires to 83 students of the Faculty of Economics and Business in Pasundan University that has been determined criteria in order to get a representative result. Methods of data analysis are multiple regression, multiple analysis, coefficient of determination analysis and hypothesis testing. The results showed that the financial, financial and student literacy in the Faculty of Economics and Business of Pasundan University was categorized as good. Simultaneously literacy and financial efficacy have a significant influence that is 85.3% of interest in investment, partially financial literacy has a significant influence that is equal to 79.9% of student investment interest and financial efficacy has a significant influence of 5.4 to interest in student investment.